A Review of Bell Pepper Production and Price Trends from 2010 to 2022 - Tara Wade; Kelvin Amon; Zhengfei Guan; Craig Frey (EDIS, 2024)
In the United States, bell peppers are cultivated for both fresh and processed markets, with California, Florida, and Georgia producing most of the crop. Production varies across states, and, in Florida, bell pepper production varies by region within the state with growing seasons ranging from July to March for northern Florida and August to February for southern Florida. This publication provides information on conventional bell pepper acreage, volume, and pricing for the top three producing states: California, Florida, and Georgia. It will be useful to producers, Extension agents, and others interested in trends concerning specialty crop commodities. It serves as a single location where important information about the specialty crop market and production trends can be found.